2021
DOI: 10.3390/plants10081671
|View full text |Cite
|
Sign up to set email alerts
|

Role of Synthetic Plant Extracts on the Production of Silver-Derived Nanoparticles

Abstract: The main antioxidants present in plant extracts—quercetin, β-carotene, gallic acid, ascorbic acid, hydroxybenzoic acid, caffeic acid, catechin and scopoletin—are able to synthesize silver nanoparticles when reacting with a Ag NO3 solution. The UV-visible absorption spectrum recorded with most of the antioxidants shows the characteristic surface plasmon resonance band of silver nanoparticles. Nanoparticles synthesised with ascorbic, hydroxybenzoic, caffeic, and gallic acids and scopoletin are spherical. Nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 119 publications
0
20
0
Order By: Relevance
“…Gold and silver-derived metallic nanoparticles (MNPs) have been shown to operate as transportation vehicles for AMPs and their conjugates, in which the functionalized nanoparticles are produced by pairing or adhesion of AMPs on the MNP surfaces ( Engin and Engin, 2019 ). These MNPs cause membrane disruption by binding to microbial surfaces through electrostatic interactions due to the large surface area and high surface charges ( Burdușel et al, 2018 ; Alzharani et al, 2021 ). Considering that most nanoparticles can concentrate in the liver, spleen, and lymph nodes, use of noble metals as resistant compounds to oxidation and erosion is an excellent option for nanoparticle production and toxicity alleviation ( Jahangirian et al, 2017 ).…”
Section: Incorporation Of Amps Into Nanoparticles and Polymersmentioning
confidence: 99%
“…Gold and silver-derived metallic nanoparticles (MNPs) have been shown to operate as transportation vehicles for AMPs and their conjugates, in which the functionalized nanoparticles are produced by pairing or adhesion of AMPs on the MNP surfaces ( Engin and Engin, 2019 ). These MNPs cause membrane disruption by binding to microbial surfaces through electrostatic interactions due to the large surface area and high surface charges ( Burdușel et al, 2018 ; Alzharani et al, 2021 ). Considering that most nanoparticles can concentrate in the liver, spleen, and lymph nodes, use of noble metals as resistant compounds to oxidation and erosion is an excellent option for nanoparticle production and toxicity alleviation ( Jahangirian et al, 2017 ).…”
Section: Incorporation Of Amps Into Nanoparticles and Polymersmentioning
confidence: 99%
“…The green Ag NPs showed different results: the main feature of the Raman spectrum obtained (Figure 2b) showed two broad bands at about 1350 cm −1 and 1565 cm −1 (marked I and II respectively) originating from the superposition of a series of vibrational modes attributable to stretching vibrations of C=C and C=O bonds [58]. This supported the presence of polyphenols involved as reducing and capping agents in Ag NPs formation [59]. In Figure 2c,d we reported the typical absorbance spectra acquired on conventional Ag NPs (Figure 2c) and green Ag NPs (Figure 2d).…”
Section: Resultsmentioning
confidence: 75%
“…At higher pH, the large number of phenolic functional groups available for silver binding facilitated a higher number of Ag + ions to bind [14]. From the study, the maximum wavelength was found to be for pH 9.…”
Section: Characterization Of Green Synthesized Silver Nanoparticles (...mentioning
confidence: 84%